2015
DOI: 10.2323/jgam.61.157
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic enzyme production by newly isolated <i>Bacillus cereus</i> SRM-001 with enhanced <i>in-vitro</i> blood clot lysis potential

Abstract: The discovery of plasmin-like microbial fibrinolytic enzymes having high specificity and negligible side effects is crucial for thrombolytic therapy. Herein, we report one such extra-cellular fibrinolytic enzyme producing Bacillus cereus SRM-001 isolated from the blood-laden soil of a chicken dump yard. The potency of the enzyme was established with fibrin plate assay and in-vitro blood clot lysis assay. The shake-flask operating parameters and media composition were optimized for maximizing the productivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…The fibrinolytic enzyme yield of 3,129 U/mL achieved in this work using the non-sterile optimized medium was significantly higher than those of relevant studies using sterile media as reported by Lee et al (1999) (1,100 U/mL), Ashipala and He (2008) (1,223.61 U/mL), Sales et al (2013) (835 U/mL), Bajaj et al (2014) (797.28 U/mL), and Narasimhan et al (2015) (1,450 U/mL). Wang et al (2008) reported higher fibrinolytic activity of 4,220 U/mL but lower productivity of 58.6 U/mL/h when compared to the current study (65.2 U/mL/h).…”
Section: Discussioncontrasting
confidence: 68%
“…The fibrinolytic enzyme yield of 3,129 U/mL achieved in this work using the non-sterile optimized medium was significantly higher than those of relevant studies using sterile media as reported by Lee et al (1999) (1,100 U/mL), Ashipala and He (2008) (1,223.61 U/mL), Sales et al (2013) (835 U/mL), Bajaj et al (2014) (797.28 U/mL), and Narasimhan et al (2015) (1,450 U/mL). Wang et al (2008) reported higher fibrinolytic activity of 4,220 U/mL but lower productivity of 58.6 U/mL/h when compared to the current study (65.2 U/mL/h).…”
Section: Discussioncontrasting
confidence: 68%
“…Biochemical characterization revealed no indole production, methyl red, or oxidase activity, while positive results were obtained for the voges-proskauer and catalase test. It utilized citrate, exhibited gelatinase and catalase activities, along with nitrate reduction, and did not show starch utilization or oxidase activity but utilized sugars with gas production [30,43]. The selected strain was further subjected to molecular characterization and was identified as Bacillus cereus RSA1 (NCBI Accession number MK288105).…”
Section: Identification and Phylogenetic Analysis Of The Strainmentioning
confidence: 99%
“…Thus, the quintessential pursuit for enhanced production of fibrinolytic protease with high efficacy has driven the statistical optimization of enzyme production. Generally, enzyme production is significantly influenced by medium components, such as nitrogen and carbon sources, and environmental aspects, such as temperature, inoculum, incubation time, and pH [42,43]. The analyses of effect of numerous physico-chemical parameters require a lot of experimentation and consumption of chemicals and time.…”
mentioning
confidence: 99%
“…The mixture is then allowed to stand at physiological temperature (37°C) for a fixed time interval, and the clot formation and its subsequent dissolution is observed (Lu et al 2010;Ju et al 2012). In addition to the mere visualisation, the percentage of clot lysis can also be determined based on the weight difference between formed clot versus lysed clot (Prasad et al 2006;Narasimhan et al 2015). This would indicate the anticoagulant nature of the test compound.…”
Section: (Howell 1964)mentioning
confidence: 99%